EMPOWERMENT OF GOAT BREEDER BUSINESS GROUP THROUGH ECONOMIC DIGITALIZATION TO INCREASE FOOD CONSUMPTION IN SUPPORTING FOOD SECURITY IN VILLAGES BLANG MIDOK, TANAH LUAS DISTRICT NORTH ACEH - Usman, Umaruddin; Erlangga, Erlangga; Likdanawati, Likdanawati; Ramadhan, Azizi; Ariski, Firli (RADJA PUBLIKA, 2021)
The main problems faced today are first, limited capital in developing a goat fattening business. Such high demand for goats is not accompanied by the provision of additional cages to place ready-made goat seeds to be fattened. Second, the lack of knowledge and understanding of good goat farming. Including the cleanliness and maintenance of the cage and even maintenance. Third, the lack of understanding of digitalization technology in running a goat fattening business. such as, making financial reports, and online marketing through existing applications. The purpose of this activity to partners is to increase the quantity of goat sales with good quality. Increased sales result in increased revenue that partners will get. Business expansion brings good changes in creating job opportunities to help this business. The method used to solve the problem is assistance such as helping to find business capital, as well as providing the latest digitalization trainings starting from the time this activity is carried out until after this activity is carried out on an ongoing basis.